2006
DOI: 10.1007/s11240-005-9070-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of transgenic Aralia elata regenerated from Agrobacterium rhizogenes-mediated transformed roots

Abstract: Transgenic hairy roots were induced from petiole and root segments of in vitro plant Aralia elata, a medicinal woody shrub, after co-cultivation with A. rhizogenes ATCC 15834. The percentage of putative hairy root induction from root segments was higher (26.7%) than petiole explants (10.0%). Hairy roots showed active production of lateral roots with vigorous elongation. Transgenic plants were regenerated from hairy roots via somatic embryogenesis. These plants had wrinkled leaves, short petioles and numerous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…However, no major alteration in leaf morphology was observed in any of the plants. Wrinkling of leaves in hairy root-transformants is common and has been reported in several species as a symptom developed after insertion of the Ri T DNA of A. rhizogenes (Chaudhuri et al 2006;Kang et al 2006). Mei et al (2001) reported wrinkle-free normal leaves in transformed plants of Alhagi pseudoalhagi.…”
Section: Resultsmentioning
confidence: 99%
“…However, no major alteration in leaf morphology was observed in any of the plants. Wrinkling of leaves in hairy root-transformants is common and has been reported in several species as a symptom developed after insertion of the Ri T DNA of A. rhizogenes (Chaudhuri et al 2006;Kang et al 2006). Mei et al (2001) reported wrinkle-free normal leaves in transformed plants of Alhagi pseudoalhagi.…”
Section: Resultsmentioning
confidence: 99%
“…Several differences were observed in the morphology and biomass of SD-and HR-R. glutinosa plants, most notably, a considerable increase in root biomass of the HR-plants. This is one of the most commonly observed properties of pRi-transformed regenerants, which was found also in such transgenic plants as Catharanthus roseus (Choi et al 2004), T. indica (Chaudhuri et al 2006), Aralia elata (Kang et al 2006) and P. indica (Gangopadhyay et al 2010). The increase is due to the influence of the introduced rol genes on hormonal synthesis and sensitivity.…”
Section: Discussionmentioning
confidence: 53%
“…Moon et al (1998) induced somatic embryogenic callus from the winter buds of 10-year-old trees incubated on Murashige and Skoog (MS) medium basal salts (Murashige and Skoog 1962) and containing 2,4-dichlorophenoxyacetic acid (2,4-D) for a period of 1 month. Kang et al (2006) induced embryogenic callus from hairy roots cultured under the same conditions as described above. Amemiya and Mochizuki (2002) obtained somatic embryogenic callus from leaflet petioles in early spring after culture on MS medium with 1.0 mg/l 2,4-D and 0.5 mg/l 6-benzyladenine (BA) for 1 month.…”
Section: Shmentioning
confidence: 99%